Improvements in cardiorespiratory fitness are not significantly associated with post-traumatic stress disorder symptom reduction in intensive treatment. Issue 1 (31st December 2019) - Voorendonk, Eline M.; Sanches, Sarita A.; De Jongh, Ad; Van Minnen, Agnes
ABSTRACT: Background : Physical activity has been found to have positive effects on symptoms of post-traumatic stress disorder (PTSD). However, the importance and role of cardiorespiratory fitness (CRF) in relation to PTSD treatment outcome is not yet clear. Objective : The purpose of the present study was to test the hypothesis that CRF would increase following intensive trauma-focused treatment (TFT) of PTSD augmented with physical activity, and that improved CRF would be associated with a significant decline in PTSD symptoms. Method : One hundred-eight individuals with severe PTSD (72% women; mean age = 40.44, SD  = 11.55) were enrolled in an intensive TFT programme of 8 days within 2 consecutive weeks that consisted of daily prolonged exposure (PE), eye movement desensitization and reprocessing (EMDR) therapy and 6 hours of physical activity each day. CRF levels were assessed at baseline and post-treatment with a 6-Minute Walk Test (6MWT) and, in a subsample, with a submaximal ergometer test (PWC75% /kg). Severity of PTSD symptoms was measured with the PTSD Symptom Scale-Self Report (PSS-SR). Results : A significant increase in CRF from pre- to post-treatment and a significant decrease of PTSD-symptoms was found. However, CRF difference scores were not associated with treatment outcome. Conclusions : Although individuals with PTSD may show an increase in CRF following an intensive TFT programme augmented with physical activity and a decrease of PTSD-symptoms, the current findings do not support the notion that treatment outcome is related to CRF. HIGHLIGHTS: PTSD patients showed markers of poor physical health at baseline. Besides PTSD symptoms, patients' CRF and blood pressure improved after 8 days of treatment. No association was found between CRF improvement and treatment outcome.